Caregiver availability for severe stroke results in improved functional ability at discharge from inpatient rehabilitation. Issue 4 (13th February 2018) - Mirkowski, Magdalena; Pereira, Shelialah; Janzen, Shannon; Mehta, Swati; Meyer, Matthew; McClure, Andrew; Speechley, Mark; Teasell, Robert
Abstract: Purpose: To evaluate the predictive capacity of caregiver availability on functional ability at time of discharge from inpatient rehabilitation in individuals with severe first-time stroke. Methods: A retrospective chart review was conducted of severe stroke inpatients admitted to a stroke rehabilitation unit between April 2005 and December 2009. Follow-up telephone interviews were conducted with patients to determine caregiver availability at time of discharge. Hierarchical linear regression analysis was performed to assess the predictive capacity of caregiver availability on functional ability at discharge from an inpatient rehabilitation unit after controlling for covariates. Results: Data from 180 individuals were included in the analysis. Individuals with a caregiver had significantly higher levels of functional ability at discharge compared to those without (85.8 ± 23.6 versus 72.9 ± 20.3; p < 0.01), although both groups achieved a minimal clinically important difference. After controlling for age, gender, admission Functional Independence Measure, and length of hospital stay, caregiver availability explained 1.3% of additional variance, with the final model explaining 41.3% of total variance for functional ability at discharge ( F (5, 174) = 26.21, p < 0.001). Conclusions: The presence of a caregiver at time of discharge from inpatient rehabilitation is predictive of significantly higher functional ability at discharge in individuals with severe stroke. Implications for rehabilitation: The availability of a caregiver at time of discharge from inpatient rehabilitation is predictive of improved functional ability at discharge in individuals with severe stroke. The presence of an available caregiver positively influences the functional recovery of individuals with severe stroke and may be an important element to successful rehabilitation.